Penentuan Ukuran Batch pada Batch Processor untuk Meminimasi Makespan - Nurprihatin, Filscha (Metris: Jurnal Sains dan Teknologi, 2016)
This research determines single-item batch sizing on a batch processor with increasing batch processing time linearly if batch size is more than critical size. The set up time of each batch is constant and it is managed before raw material exist on a machine. The decision variables in this research are the number of batches and batch sizes to minimize makespan. This research assumes all orders have to be delivered to the customer at the same time (common due date). This research also develops an algorithm for common due date case studies. The resulted model development can solve the batch sizing problem and the quality of solution is feasible. For demand 125 tons and the capacity of a batch is 50 tons, then